Nicolas Bourriaud : relational aesthetics - Bourriaud, Nicolas; Pleasance, Simon; Woods, Fronza; Copeland, Mathieu (France : Les presses du réel, 2010)
Relational form -- Contemporary artistic practice and its cultural plan ; Artwork as social interstice ; Relational aesthetics and random materialism ; Form and others' gaze -- Art of the 1990s. Participation and transitivity ; Typology ; Connections and meetings ; Convivialities and encounters ; Collaborations and contracts ; Professional relations : clienteles ; How to occupy a gallery -- Space-time exchange factors -- Artworks and exchanges ; The subject of the artwork ; Space-time factors in 1990s' art -- Joint presence and availability : the theoretical legacy of Felix Gonzalez-Torres -- Homosexuality as a paradigm of cohabitation ; Contemporary forms of the monument ; The criterion of co-existence (works and individuals) ; The aura of artworks has shifted towards their public ; Beauty as a solution?. Screen relations -- Today's art and its technological models ; Art and goods. The law of relocation ; Technology as an ideological model (from trace to programme) ; The camera and the exhibition ; The exhibition-set ; Extras ; Post VCR art ; Rewind/play/fast forward ; Towards a democratisation of viewpoints? -- Towards a policy of forms -- Cohabitations : notes on some possible extensions of a relational aesthetics ; Visual systems ; The image is a moment ; What artists show ; The boundaries of individual subjectivity ; The engineering of intersubjectivity ; An art with no effect? ; The political development of forms ; Rehabilitating experimentation ; Relational aesthetics and constructed situations ; The aesthetic paradigm (Félix Guattari and art) ; Subjectivity pursued and produced ; De-naturalising subjectivity ; Status and operation of subjectivity ; Subjectivization units ; The aesthetic paradigm ; The critique of scientistic paradigm ; Ritournelle, symptom and work ; The work of art as partial object ; For an artistic-ecosophical practice ; The behavioural economy of present-day art
CCS Gent
boek
Keywords: Bourriaud, Nicolas